The Values of Qaulan Sadida of Islamic Communication on Bidadari Bermata Bening Series - Khairina, Ulfa; Heri Rahmatsyah Putra; Irsan Adrianda; Junaidi; Mutia Tisa; Iin Meriza; Hijrah (Darul Ilmi Bina Insan Foundation, 2023)
Islamic communication values are not only be obtained from daily interactions between communicators and communicant, but also from screen media, such as web series. The web series entitle Bidadari Bermata Bening is an Islamic novel that contains the values of qaulan sadida (telling the truth) in everyday life. This research aims to look at the values of qaulan sadida in the Bidadari Bermata Bening web series as part of Islamic communication. This research uses a qualitative analysis technique. Data search was carried out using a web series documentation technique of ten episodes. The results of this research show that qaulan sadida in this web series is applied in the Islamic boarding school educational environment, relationships between characters, friendship, business practices, and the personality of the main character in the story.